MARKETING AUDIT OF DOKTER SOEDARSO HOSPITAL BASED ON STRATEGIC MARKETING PLUS 2000 - Muhaimenon Muhaimenon; Barkah Barkah; Erna Listiana (Jurnal Ekonomi, 2023)
This research is motivated by the existence of a gap where Doctor Soedarso Hospital has not become the main choice of the people of Pontianak City when they need health services even though this hospital scores the Community Satisfaction Index (IKM) in the good category, lower service rates than private hospitals and has superior resources. Power. As for goals study This is For get an overview of the marketing strategy of Doctor Soedarso Hospital which includes the orientation/type of marketing and the competitive situation in the next 5 (five) years based on the results of the strategic marketing plus 2000 audit. Method study Which The case study method used is a quantitative-qualitative approach using a marketing strategy audit plus 2000 by calculating the Company Alignment Index (CAI) and Competitive Setting Index (CSI) and comparing the values of both (gap analysis). Calculation of the two indices obtained from the results of the questionnaire based on the level of confidence of the respondents who manage marketing policy at Doctor Soedarso Hospital. From the results of the analysis it is known that the CSI value is 3.9 and the CAI value is 2.9, the gap analysis shows that there is a negative gap of 1.0 where the CAI <CSI value means that the marketing strategy of Doctor Soedarso Hospital is still lagging behind compared to the challenges competitive situation in the next five years. According to the framework Strategic Marketing Plus 2000 , CAI values ranging from 2.6 to 3.4 shows that currently the marketing orientation type of RSDS is included in type 3C that is marketing segmented. Therefore, it is necessary to develop a marketing strategy design for Doctor Soedarso Hospital by changing the orientation the marketing from form 3C ( marketing oriented ) become 3.5C ( market driven ) in accordance with situation competition 3.5C ( sophisticated ) to be faced for the next five years.